MILLENNIAL FINANCIAL ATTRIBUTES: STRUCTURAL MODELLING APPROACH - Hakim, Lukmanul; Syafitri, Ridha (PATTIMURA UNIVERSITY, 2022)
This study aims to determine the influence of Financial Literacy on electronic financial transaction decisions, the influence of financial management behavior on electronic financial transaction decisions, the influence of financial attitude on electronic financial transaction decisions, the influence of inclusion on electronic financial transaction decisions, the influence of transaction decisions electronic finance against consumptive behavior. This type of Research is Survey Research with Quantitative Approach. The samples used in this study were 96 samples with sampling techniques using non-probability and purposive sampling techniques. The data analysis technique used is Structural Equation Modeling (SEM). The results of this study show that financial literacy on electronic financial transaction decisions, financial management behavior towards consumptive behavior, financial attitude towards electronic financial transaction decisions and electronic financial transaction decisions towards consumptive behavior have a significant effect. Meanwhile, financial literacy towards consumptive behavior, financial management behavior towards electronic financial transaction decisions, financial attitude towards consumptive behavior, inclusion of electronic financial transaction decisions and inclusion of consumptive behavior have no significant effect.